Education for peace and a pedagogy of hope - Carl, AE (South African Journal of Higher Education, 2011)
There are many approaches and arguments on how hope could be given to children in a society characterised by violence and conflict, hope that may contribute towards optimising their potential. This article focuses on the notion and meaning of Peace Education, what the possible link between Peace Education and a Pedagogy of Hope might be and lastly, on what the curriculum implications are for the school and the teacher. I argue that it is through relevant curriculum development that the aims of Peace Education and thus the promotion of hope, can be promoted and achieved. Schools and educators are key role-players in this process as the future of society depends on the children of today. These role-players therefore have to be enabled and empowered with appropriate skills and knowledge to achieve this vision of giving people hope. . . . since wars begin in the minds of men, it is in the minds of men that defences of peace must be constructed (Heater 1985, 2666).